2021
DOI: 10.1007/s12524-020-01300-7
|View full text |Cite
|
Sign up to set email alerts
|

UAV-Based Survey of Glaciers in Himalayas: Challenges and Recommendations

Abstract: Unmanned Aerial Vehicle (UAV) based remote sensing (RS) studies in glaciology are mainly focusing on obtaining accurate high-resolution data from UAV images. Studies for identifying and minimising the challenges faced during the UAV-based RS data acquisition survey on inaccessible and harsh terrains of mountain glaciers is limited. This study aims to examine the practical challenges faced during UAV surveys of glaciers and derive strategies to minimize them. To the authors' knowledge, this is the first study t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This may be an optimistic estimate when considering the heterogeneity of applications globally due to differences in operational expenses, transportation time, and local regulations. Additionally, weather conditions and flight performance at different altitudes [60] may affect the flight speed and hence impact costs. We encourage the use of the calculations presented in Appendix A.5 to create estimates for a specific data collection process.…”
Section: Cost Analysis: Resultsmentioning
confidence: 99%
“…This may be an optimistic estimate when considering the heterogeneity of applications globally due to differences in operational expenses, transportation time, and local regulations. Additionally, weather conditions and flight performance at different altitudes [60] may affect the flight speed and hence impact costs. We encourage the use of the calculations presented in Appendix A.5 to create estimates for a specific data collection process.…”
Section: Cost Analysis: Resultsmentioning
confidence: 99%
“…In their study, Ramsankaran et al [140] summarized various challenges for surveying glaciers and found that the choice of UAV launch/landing sites afects the survey and recommended selection criteria for the most suitable launch/ landing sites. Snow-covered surfaces pose photogrammetric challenges as there is a lack of contrast and the surface refectance is very high.…”
Section: Urban Storm Water Mcdonaldmentioning
confidence: 99%
“…Drone-based monitoring can easily overcome those limitations. The potential for using drones in glaciology is huge, and drones could play a great supporting role in field-based and satellite remote sensing-based glaciology observations [28][29][30][31][32][33]. Glaciers located in high mountainous areas are always under harsh conditions, such as having a hostile climate or poor approachability, and this is a huge limitation in field observations along with inadequate labor and funding, creating great difficulties in the dynamic research on layers.…”
Section: Introductionmentioning
confidence: 99%